The legitimation of wife abuse among women: the impact of belief in a just world and gender identification - Correia, I.; Alves, H.; Morais, R.; Ramos, M. (Personality and Individual Differences, 2015)
Past research has found that when victims are ingroup members, observers' social identification interacts with general belief in a just world (GBJW) to predict judgments about those victims. In this correlational study (N = 284 women, ages from 18 to 80) we aimed to test whether and how women's explicit endorsement of BJW, both personal belief in a just world (PBJW) and GBJW, interacts with their identification as women to predict wife abuse legitimization. We predicted and found that the interaction between PBJW and social identification predicted legitimization of wife abuse. Specifically, for highly identified women, PBJW was positively associated with wife abuse legitimization, for less identified women, PBJW was not associated with wife abuse legitimization. This interaction was significant above and beyond other variables associated with this phenomenon: hostile and benevolent sexism, empathy (cognitive and emotional), and social desirability. On the contrary, the interaction between GBJW and social identification was a nonsignificant predictor of legitimization of wife abuse. These results contribute to reconceptualize the role of PBJW and GBJW on judgments about victims and to highlight the importance of considering the victimization situations in the social context and the social groups in which they actually occur.